Improved dielectric properties and grain boundary response of SrTiO3 doped Y2/3Cu3Ti4O12 ceramics fabricated by Sol-gel process for high-energy-density storage applications. Issue 15 (December 2017) - Peng, Zhanhui; Li, Junwei; Liang, Pengfei; Yang, Zupei; Chao, Xiaolian
Abstract: A chemical solution processing method based on sol-gel chemistry (SG) was used to synthesize (1- x )Y2/3 Cu3 Ti4 O12 - x SrTiO3 ( x  = 0, 0.05, 0.1, 0.15, 0.2, 0.25) ceramics successfully. The 0.85Y2/3 Cu3 Ti4 O12 -0.15SrTiO3 ceramics sintered at 1050 °C for 20 h showed fine-grained microstructure and high dielectric constant ( ε′  ≈ 1.7 × 10 5 ) at 1 kHz. Furthermore, the 0.85Y2/3 Cu3 Ti4 O12 -0.15SrTiO3 ceramics appeared distinct pseudo-relaxor behavior. Two electrical responses were observed in the combined modulus and impedance plots, indicating the presence of Maxwell-Wagner relaxation. Sr vacancies and additional oxygen vacancies had substantial contribution to the sintering behavior, an increase in grain growth, and relaxation behaviors in grain boundaries. The contributions of semiconducting grains with the nanodomain and insulating grain boundaries (corresponding to high-frequency and low-frequency electrical response, respectively) played important roles in the dielectric properties of (1- x )Y2/3 Cu3 Ti4 O12 - x SrTiO3 ceramics. The occurrence of the polarization mechanism transition from the grain boundary response to the electrode one with temperature change was clearly evidenced in the low frequency range.